Attitude, Behavior and Oral Health among Patients Visiting a Dental Institution of Nepal - Dahal, Sirjana; Poudel, Prakash; Khadka, Nirrma; Dahal, Sangita; Acharya, Manita; Shrestha, Supriya; Maharjan, Manita (Journal of College of Medical Sciences-Nepal, 2020)
Background: Majority of oral diseases are related to life style, which means that a behavioral change is needed to reduce the disease. This study was conducted to assess the attitude, behavior and oral health of the patients visiting a dental hospital and association of oral health with age and gender. Methods: A cross-sectional study was conducted among 130 patients of 15 years and above who visited Kathmandu medical college, Bhaktapur for oral health check-up. Participants were interviewed for their attitude and behavior regarding oral health. Caries experience and periodontal conditions were assessed. Chi square test was done to evaluate the association age and gender with of attitude, behavior and oral health. Results: In this study, significantly higher number of females went to visit dentist when they noticed bleeding gums than males (p=0.023). Tobacco was consumed more by males than females (p<0.001). Mean DMFT was 3.85±3.035. Bleeding on probing was found in 64.6%; calculus in 18.5% and periodontal pocket of ≥4mm in 11.6%. Loss of attachment of 4mm or more was present in 34.6% and was significantly higher in older age group (p<0.001); in males (p=0.001); who were negligent in visiting dentist (p=0.035); brushed by vertical method (p=0.013) for less than two minutes and more than five minutes (p=0.015); used toothpicks or no interdental cleaning aids (p=0.009); ignored bleeding gums (p=<.001) and who used tobacco products (p<0.001). Conclusions: This study concluded that the attitude towards the oral health was positive among the patients who visited Kathmandu Medical College, Bhaktapur, Nepal. The oral health behaviour was quite unsatisfactory and needs to be improved.